Nearbyou: a crowdsourced app for finding the best places for peace and quiet - Lee, Xuanhui (Nanyang Technological University, 2023)
In recent years, the use of mobile devices and mobile applications has become ubiquitous in our daily lives [1]. This trend has given rise to many navigation-related applications that serve different purposes. These applications aim to make navigation more personal and more accessible. When it comes to navigation, Google Maps is the dominant force in the market [2]. However, its focus can be too broad and can make navigation with specific requirements more challenging. In this context, our project focuses on developing a mobile application, Nearbyou, using the Flutter framework which allows users to find peaceful and quiet places around their city, provide relevant insights into the location and assist them in navigation. The application works by allowing users to create/view geotags of a location that comes with location details as well. Users can also use the Global Positioning System (GPS) to create their own path/trail while recording it using video. Users can then view the content generated by other users through an explore page and contact the content creator through a private chat. Many scientific studies have been done on why peaceful and quiet environments are essential for human well-being [3-5]. Studies have also shown that noise pollution in urban areas is a critical and growing problem; it is linked to detrimental effects on physical and mental health [6-10, 16-19]. Therefore, solutions to tackle or alleviate this problem are necessary. In this research, we aim to contribute to the field of navigational applications by developing a mobile application that assembles a compilation of quiet places and traces the user’s path that does not restrict users to conventional roads and sidewalks. By successfully implementing our proposed application, we hope to demonstrate the potential of Flutter and provide users with a unique and personal experience as they seek out quiet places in our hectic world. Keywords: Mobile interaction, geotagging, navigation, peaceful and quiet places